FEVR combined with macular heterotopia in children presenting as pseudo-exotropia: a case report and literature review - Zhang, Yujie; Chen, Shuimiao; Xiu, Yanghui (Frontiers in Medicine, 2024)
Familial exudative retinopathy (FEVR) is a hereditary disease involving abnormal retinal vascular development in which macular heterotopia (MH) caused by mechanical-like pulling of the vitreous may lead to pseudo-strabismus. We describe the case of a 12-year-old male patient from China who presented to our hospital with a request for surgical correction of exotropia. Examination revealed that the strabismic appearance was due to MH, and dilated pupil examination of the peripheral fundus revealed that the blood vessels of the left eye and the macula were displaced toward the temporal retina by pulling, and further FFA examination was performed to diagnose FEVR. With good binocular vision and stereoscopic distance vision, corrective surgery for strabismus in this patient would have resulted in a hard-to-resolve diplopia. Therefore, it is important to identify FEVR combined with MH in clinical practice to avoid wrong diagnostic and treatment options.